2018
DOI: 10.1039/c7tb03213g
|View full text |Cite
|
Sign up to set email alerts
|

Potential application of an injectable hydrogel scaffold loaded with mesenchymal stem cells for treating traumatic brain injury

Abstract: In this contribution, we developed an injectable hydrogel composed of sodium alginate and hyaluronic acid that acts as a tissue scaffold to create a more optimal microenvironment for the stem cells for potential application of traumatic brain injury implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 41 publications
4
73
0
Order By: Relevance
“…A temperature scan with a heating rate of 2/min from 17°C to 90°C was performed, the analysis frequency was 1 rad/s, and the change curves of the G ′, G ″, phase angle, and complex viscosity were recorded; the intersection of G ′ and G ″ is defined as gelation temperatures ( T gel , Chenite, 2000). The morphology of the gelling hydrogel was observed by scanning electron microscopy (QUANTA200, Holland FEI, The Netherlands) after freeze‐drying and gold spraying (Zhang, Shi, et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A temperature scan with a heating rate of 2/min from 17°C to 90°C was performed, the analysis frequency was 1 rad/s, and the change curves of the G ′, G ″, phase angle, and complex viscosity were recorded; the intersection of G ′ and G ″ is defined as gelation temperatures ( T gel , Chenite, 2000). The morphology of the gelling hydrogel was observed by scanning electron microscopy (QUANTA200, Holland FEI, The Netherlands) after freeze‐drying and gold spraying (Zhang, Shi, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, tissue engineering is widely recognized as a hot topic in the field of biomedical science, and it is playing more and more crucial roles for organ/tissue repair and replacement (Caccavo, Cascone, Lamberti, & Barba, ). Current technologies have achieved the aims of implanting the biomaterials loaded with the massive in vitro cultured cells into the human body in order to restore, replace, maintain, or improve the function of tissues or organs (Zhang et al, ). However, only a few engineered tissues or organs have clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, hydrogels have been widely used in tissue engineering and nerve regeneration due to their good biocompatibility, water retention and drug‐delivery properties . Ortuno‐Lizaran et al fabricated biodegradable hyaluronic acid hydrogel conduit by chemical cross‐linking, and found that Schwann cells could grow well in the conduit lumen.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, hydrogels have been widely used in tissue engineering and nerve regeneration due to their good biocompatibility, water retention and drug-delivery properties. [18][19][20][21][22][23][24] Ortuno-Lizaran et al 25 fabricated biodegradable hyaluronic acid hydrogel conduit by chemical cross-linking, and found that Schwann cells could grow well in the conduit lumen. Gonzalez-Perez et al 26 prepared collagen hydrogel-filled chitosan conduits containing extracellular matrix, the conduit could promote the repair of peripheral nerve injury to a certain extent, which may be used as a potential candidate in the repair of peripheral nerve injury.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the modified layers' biomechanical properties, the stress values of each sample were detected by a microcomputer controlled electronic universal testing machine (WDW_200, Shanghai Hualong testing instrument Limited by Share Ltd., Shanghai, China). The weight loss of all the samples was also measured to evaluate the layers' biodegradability properties [20].…”
Section: Characterization Of Pda/pei/5-fu Layersmentioning
confidence: 99%